2010
DOI: 10.3109/02699052.2010.506855
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intensive repetition of a new facilitation technique on motor functional recovery of the hemiplegic upper limb and hand

Abstract: ObjectiveTo study the effects on the hemiplegic upper limb of repetitive facilitation exercises (RFEs) using a novel facilitation technique, in which the patient's intention to move the hemiplegic upper limb or finger was followed by realization of the movement using multiple sensory stimulations.MethodsTwenty-three stroke patients were enrolled in a cross-over study in which 2-week RFE sessions (100 repetitions each of five-to-eight types of facilitation exercise per day) were alternated with 2-week conventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
43
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(47 citation statements)
references
References 27 publications
2
43
2
Order By: Relevance
“…These devices allow time-specific tasks to be executed repeatedly in a controlled and reliable way, as this has been shown to be a determining factor in facilitating cortical reorganization, allowing a concomitant increase in motor ability and improved functional activity performance (Liepert, 2006). Recent evidence has shown that intensive repetition of movements could make a useful contribution to clinical practice (Kawahira et al, 2010), constituting a promising approach for patients affected by motor impairments due to neurological diseases, such as multiple sclerosis (Gijbels et al, 2011), cervical spinal cord injuries (Zariffa et al, 2012), and chronic stroke (Krebs et al, 2002;Macclellan et al, 2005;Sanchez et al, 2006;Masiero et al, 2007;Colombo et al, 2008;Kwakkel et al, 2008). Indeed, the use of devices designed to intensify therapy in the single patient could be a promising field of investigation (Masiero et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…These devices allow time-specific tasks to be executed repeatedly in a controlled and reliable way, as this has been shown to be a determining factor in facilitating cortical reorganization, allowing a concomitant increase in motor ability and improved functional activity performance (Liepert, 2006). Recent evidence has shown that intensive repetition of movements could make a useful contribution to clinical practice (Kawahira et al, 2010), constituting a promising approach for patients affected by motor impairments due to neurological diseases, such as multiple sclerosis (Gijbels et al, 2011), cervical spinal cord injuries (Zariffa et al, 2012), and chronic stroke (Krebs et al, 2002;Macclellan et al, 2005;Sanchez et al, 2006;Masiero et al, 2007;Colombo et al, 2008;Kwakkel et al, 2008). Indeed, the use of devices designed to intensify therapy in the single patient could be a promising field of investigation (Masiero et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Repetitive facilitation exercises (RFEs) are effective physiotherapy for hemiplegic limbs (12,13). RFEs for upper limbs and fingers provide sufficient physical stimulation (such as stretch or skin-muscle reflexes elicited immediately before movements) to elevate the level of excitation of corresponding, injured, descending motor tracts; this allows patients to initiate their intended movements.…”
Section: Introductionmentioning
confidence: 99%
“…With the decreased levels of physical activity participation, an individual with hemiplegia may encounter loss of physical fitness (Chen, Ashtonmiller, Alexander, & Schultz, 1991;Harada, Chiu, & Stewart, 1999;Mayo et al, 1999), metabolic decline (Ivey, Hafer-Macko, & Macko, 2008), and lack of motor skills (Kawahira et al, 2010), as well as difficulty in performing activities of daily living (Koc & Kilic, 2013). In addition, people with hemiplegia often tend to have problems associated with psychosocial variables such as depression, selfconfidence, and social skills, which all together eventually impact the quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have shown that exercise has positive impact on hemiplegic gait and lower limb (Babalola & Taiwo, 2011;Gharib, El-Masksoud, & Rezk-Allah, 2011;Kawahira, Shimodozono, Ogata, & Tanaka, 2004;Yosuke et al, 2010), upper extremity functioning (Kawahira et al, 2010;Park et al, 2012), posture (Baek, Kim, Kim, Oh, & Yoo, 2009;Gray, Juren, Ivanova, & Garland, 2012), functional skills for ADLs (Koc & Kilic, 2013), and balance (Olawale & Ogunmakin, 2006). Also, evidence shows that participation in an adapted physical activity program can induce decreasing the degree of depression, as well as improving mobility functioning .…”
Section: Introductionmentioning
confidence: 99%